Multiple episodes of hematite mineralization indicated by U-Pb dating of iron-ore deposits, Marquette Range, Michigan, USA - Rasmussen, B.; Zi, J.; Sheppard, S.; Krapež, B.; Muhling, Janet (Geological Society of America, 2016)
© 2016 Geological Society of America.High-grade hematite ore (so-called "hard ore") was first mined in the Lake Superior region of North America in A.D. 1848. The development of ore deposit models from the region has strongly influenced research on the origin of this deposit type worldwide. The inability to date high-grade hematite ores has hindered the testing of competing genetic models. In the Marquette Range, northern Michigan (USA), high-grade hematite ore is hosted by the 1.9-1.85 Ga Negaunee Iron Formation and unconformably overlying Goodrich Quartzite. Field relations and new in situ U-Pb geochronology of monazite and xenotime intergrown with hematite from six mines across the Marquette Range, Michigan, indicate that the formation of high-grade hematite ore bodies involved up to three events. The presence of pebbles of hematite ore in basal conglomerate of the Goodrich Quartzite indicates that the first episode of iron-oxide mineralization occurred after deposition and deformation of the Negaunee Iron Formation, but before the ca. 1.85 Ga Sudbury impact. Monazite in iron-ore deposits within the hinges of Penokean-aged folds yields an age of ca. 1.8 Ga, which is interpreted to record a second phase of hematite enrichment. Monazite and xenotime in iron-ore deposits along the limbs of regional folds give ages of ca. 1.77 Ga and are interpreted to record a later episode of hematite upgrading. The ca. 1.8 Ga and ca. 1.77 Ga phosphateages coincide with the timing of regional tectonic events, suggesting hematite mineralization was coeval with the Penokean orogeny andYavapai-interval accretion. Our results support the proposal that the formation of high-grade hematite ore bodies is a multistage process linked to discrete orogenic events.